Pengaruh penyajian laporan keuangan daerah dan aksesibilitas terhadap penggunaan informasi keuangan daerah (studi pada provinsi riau) - Ramadhani, Yesi; Taufik, Taufeni; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine examine whether the accessibility of local financial reports and presentation of them influence the usefulness of local financial information by the stakeholders. The population in this study is 580 people usefulness financial reports in Riau Provincial Government is DPRD, BPK, LSM. Samples in this study is 85 responden has already accomplish sample criterion. Data collection techniques are used by distributing questionnaires.The results showed that the effect of persentation of local financial reports on the usefulness of local financial information. This can be seen from the significant value of 0.040 < 0.05. Accessibility on the usefulness of local financial information. Evidenced by the significant value of 0.000 < 0.05.Adjusted R Square value of 0.371. this means that 37.10% of usefulness of local financial information variables can be explained by the presentation of local financial reports and accessibility. While the remainder is equal to 62.90% is explained by other variables outside the investigated.Keywords: local financial reports, accessibility, local financial information